O gênero na escola: a educação física em questão. - SANTOS, Jeferson Moreira do (2008)
Schools are important places for the formation of identities, as students stay there four hours per day, 200 days per year, for many years of their lives, during childhood, adolescence and adulthood. In this environment, physical education is distinguished as the discipline which works systematically with the elements of the corporal culture. During the accomplishment of this dissertation, I perceived that the way by which teachers and students conceive the objectives of the lessons of physical education influences directly in the way gender questions are shown in pedagogical practice. When the conceptions of the classes are merely linked to the aspect of sports teaching, working with emphasis only in physical valences - force and agility -, the participation and the learning of female students and of those students who do not correspond to the standards of hegemonic masculinity is decreased. Therefore, the reorganization of the classes seems important, regarding the diversification of the contents of lessons and the way by which they are taught, in order to promote the learning of all the students, instead of the non-critical reproduction of physical activities that can be carried through in any social space, disarticulated from the values that guide the pedagogical proposal of the school. At last, but not less important, the research demonstrated that female students feel a sort of fear during the classes and that they would prefer that the students were separated by their biological gender in these classes, as a way of guaranteeing their physical integrity. However, this does not mean that this separation is the only way (neither it is the most desirable) to guarantee the participation and the learning of the female students, as these objectives can be reached by a gender equity orientated performance of the professors, including the physical education ones.